1982
DOI: 10.1207/s15327752jpa4601_12
|View full text |Cite
|
Sign up to set email alerts
|

Three Measures of Locus of Control: What Do They Measure?

Abstract: The Rotter, Adult Nowicki-Strickland, and Levenson IE scales were completed by 175 undergraduate students. Factor analyses reconfirmed the factor structure of the Levenson IE scale. Partial correlation analyses showed that the portion of common variance shared by the Rotter IE and the Adult Nowicki-Strickland IE scales associated closely with Levenson's Chance factor. These findings support a multi-dimensional view of locus of control attribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 3 publications
2
12
0
2
Order By: Relevance
“…The original six-point scale was adapted to a ®ve-point Likert scale, with anchors of strongly disagree and strongly agree. Previous research has indicated that this scale possesses adequate levels of construct validity and internal consistency (Levenson, 1981;Lindbloom and Faw, 1982;Sherman and Ryckman, 1980;Kapoor and Ansari, 1988;Kapoor et al, 1986).…”
Section: Locus Of Controlmentioning
confidence: 95%
“…The original six-point scale was adapted to a ®ve-point Likert scale, with anchors of strongly disagree and strongly agree. Previous research has indicated that this scale possesses adequate levels of construct validity and internal consistency (Levenson, 1981;Lindbloom and Faw, 1982;Sherman and Ryckman, 1980;Kapoor and Ansari, 1988;Kapoor et al, 1986).…”
Section: Locus Of Controlmentioning
confidence: 95%
“…To date, studies indicate that results might be more consistent, at least for some specific drugs, if perceived control is differentiated into multiple dimensions. Work such as that by Dielman, Campenelli, Shope, and Butchart (1987) and Lindbloom and Faw (1982) help to clarify the utility of using multidimensional instruments relative to adolescent substance use. In LOC studies that have used multidimensional LOC instruments with a health focus, specifically either the Health Locus of Control (HLC) scale (Wallston, Wallston, Kaplan, & Maides, 1976), or the Children's Multidimensional Health Locus of Control (CMHLC) scale (Parcel & Meyer, 1978), small but significant relations between LOC and substance use have been found (Carter, Denson, & Randow, 1985;Dielman et al, 1987).…”
Section: Pathsmentioning
confidence: 99%
“…Os itens de mensuração desse fator endereçam apenas a questão da atribuição da sorte em relação à porção de controle de forças externas que é percebida pelo empreendedor. Como apontado anteriormente, a escala de Levenson apresenta um outro fator denominado controle pelo poder de outros (LINDBLOOM;FAW, 1982). Como não se identificou essa dimensão nas entrevistas da fase preparatória, o fator não foi considerado.…”
Section: Discussão Dos Resultadosunclassified
“…B. Rotter (KAUFMANN; WELSH, LOOSEMORE;LAM, 2004). Desde então, o construto tem servido como objeto de análise e também como fator explicativo para a variação de uma série de variáveis dependentes em estudos de diversas disciplinas, tais como psicologia (FERGUSON, 1993;OLIVER;JOSE;BROUGH, 2006;SPECTOR, 1988;TAMAYO, 1989) Em relação a esses estudos, é possível perceber que o conceito tem passado por certa evolução no desenvolvimento de distintas medidas desde sua apresentação inicial (LINDBLOOM;FAW, 1982). As escalas de mensuração mais comuns são: 1. de Rotter, 2. de Nowicki e Strickland e 3. de Levenson.…”
Section: Definição E Formas De Mensuração De Lócus De Controleunclassified